1995
DOI: 10.1002/hep.1840210123
|View full text |Cite
|
Sign up to set email alerts
|

Octreotide blunts postprandial splanchnic hyperemia in cirrhotic patients: A double-blind randomized echo-doppler study

Abstract: The effect of octreotide, a long-acting synthetic analog of somatostatin, on fasting and postprandial splanchnic hemodynamics was investigated in cirrhotic patients. Splanchnic hemodynamics were assessed using an echo-Doppler duplex system in a prospective, double-blind, placebo-controlled, crossover study performed on 2 separate days, 1 week apart, in 30 cirrhotic patients. Measurements of portal vein (PV) cross-sectional area (PV-A) and mean velocity (PV-V), and of superior mesenteric artery (SMA) mean veloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 21 publications
2
39
0
2
Order By: Relevance
“…E, Patients with HRS Type 1; F, patients with HRS type 2. [14][15][16][17] or no change in these parameters. 18 These differences may be related to the dosage of the drug, the route of administration (intravenous or subcutaneous), the duration of treatment, the techniques used to measure splanchnic blood flow, and the degree of liver failure in the cirrhotic patients.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…E, Patients with HRS Type 1; F, patients with HRS type 2. [14][15][16][17] or no change in these parameters. 18 These differences may be related to the dosage of the drug, the route of administration (intravenous or subcutaneous), the duration of treatment, the techniques used to measure splanchnic blood flow, and the degree of liver failure in the cirrhotic patients.…”
Section: Discussionmentioning
confidence: 95%
“…23 We did not find any decrease in fasted glucagon plasma levels after octreotide infusion. Previous studies have shown that octreotide could reduce glucagon plasma levels after acute intravenous 17 or subcutaneous administration 14 or after chronic subcutaneous administration. 24 This discrepancy can be related to the severity of liver failure observed in our patients or to a desensitization to the effects of octreotide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 It has also been shown that octreotide blunts this postprandial increase both in normal subjects 20,21 and cirrhotic patients. [22][23][24] Recently, a new long-acting somatostatin analog, lanreotide, has been developed. 25 The hemodynamic effects of this peptide in humans are yet unknown.…”
mentioning
confidence: 99%
“…It might be blunted by octreotide and isosorbide-5-mononitrate (ISMN), whereas propranolol decreases only baseline HVPG [37][38][39][40].…”
Section: Recommendationsmentioning
confidence: 99%